A simplified methodology to simulate a heat exchanger in an aircraft's oil cooler by means of a Porous Media model. (5th February 2016) - Musto, Marilena; Bianco, Nicola; Rotondo, Giuseppe; Toscano, Flavio; Pezzella, Giuseppe
Highlights: CFD simulation of aircraft turboprop's oil cooler exchanger by means of Porous Media. Comparison between experimental data and CFD results. Porous Media model is used to simulate the HE main effects (pressure drop, heat rejection). Abstract: This work describes a simplified methodology to model (air-side) a heat exchanger within a computational fluid dynamics analysis of an oil cooler device for aerospace applications. Although several CFD solvers provide specific tools to simulate a heat exchanger, sometimes the available data, as for example, cooling plate geometries, dimensions and their arrangement in the heat exchanger, are not exhaustive enough to set up the numerical simulation. Hence, in the present research was used a porous media model to simulate the main effects of the heat exchanger, such as pressure drop and heat rejection, on the flowfield occurs place inside an aircraft oil cooler system. In this way, the need to model the real complex geometry of the heat exchanger is avoided. In this framework, present analyses aim at verifying that the heat exchanger, under investigation, is able to satisfy the system requirements in terms of heat rejection of the engine's oil cooling system, foreseen for the aircraft operating conditions. In particular, the paper analyzes a turboprop oil cooler heat exchanger when the aircraft is flying at cruise conditions, namely 2743 m (9000 ft) altitude, focusing attention on several heat exchanger flow field features such as air pressure drop, temperature change and mass flow rate. Finally, those numerical results are analyzed in detail and compared to experimental data available for the heat exchanger, thus pointing out that this design approach represents a viable option in the framework of oil cooling heat exchanger performance investigation.